Pharmacists’ Experiences and Needs in Pharmaceutical Care to Support Diabetes Medication Adherence in Indonesian Primary Care - Riza Alfian; Muhammad Hafizh Abiyyu Fathin Fawwazi; Wirawan Adikusuma; Yohane Vincent Abero Phiri (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2026)
Introduction: Medication adherence remains a major challenge in the management of diabetes mellitus, particularly in primary health care. Pharmacists play an important role in supporting adherence through pharmaceutical care. However, there is still limited evidence regarding pharmacists’ experiences and needs in implementing pharmaceutical care related to adherence in community health centers (Puskesmas) in Indonesia. Methods: This descriptive cross-sectional study was conducted among pharmacists working at Community Health Centers (Puskesmas) in South Kalimantan Province, Indonesia, between July and August 2025. A total of 244 pharmacists were invited, and 161 participated (response rate 66.0%). Data were collected using a validated structured questionnaire consisting of 35 items on a five-point Likert scale, covering pharmacists’ experiences, barriers, and needs in implementing pharmaceutical care to support medication adherence among patients with diabetes mellitus. Data were analyzed descriptively. Results: Pharmacists predominantly relied on indirect adherence assessment, most commonly through prescription refill monitoring (60.9%), while less consistently confirming patients’ understanding of therapeutic goals. Adherence-support interventions were largely limited to face-to-face education, with minimal use of remote/digital modalities (telephone or social media: 60.9% never). Monitoring and follow-up were also inconsistent, including limited assessment of adverse drug reactions. Key systemic and workflow barriers included limited time, lack of training, and restricted access to patients’ clinical information (75.8%). Pharmacists reported strong needs for standardized adherence assessment tools, accessible patient medication records, systematic guidelines, and training programs. Conclusion: Pharmaceutical care to support medication adherence among patients with diabetes mellitus in Puskesmas is not yet implemented consistently. Strengthening pharmacist competencies through practical tools, clear guidance, and continuous training, together with better access to patient information and appropriate use of digital resources, may improve the delivery of adherence services in primary care.